Evaluation of the Microlocal Wind Power Potential for the Operation of a University Wind Turbine - Villamarín Guerrero, Luis Fernando; Mayorga Betancourt, Manuel Alejandro; Amaris Mendoza, María Camila; Herrera Martínez, Marcelo; Sánchez Tachack, David Ricardo (TECCIENCIA, 2017)
The research deals with the estimation of the available wind’s potential on the building terrace, at the P -headquarter of the Universidad ECCI of Colombia, and from the results obtained consequently verify if the wind conditions are conducive to the operation of a wind micro-turbine, currently unused. The methodology is based on the wind speed estimation; applying the velocity potential’s law to the records captured, between the 1st of January and the 24th of March, 2015, by the weather station of the National University of Colombia. Once the speed of the wind is estimated in the study area, a frequency velocity distribution is performed and the graphical method is applied to determine the scale and shape parameters that allow the characterization of the function of the Weibull distribution in the study area. Finally, based on the micro turbine’s specifications, the power that could be usable is estimated and it is theoretically evaluated if the wind conditions are opti mal for its operation. Although wind speed data were recorded in the study area, using the Universidad ECCI weather station, they were only used as a benchmark for the estimated velocities. The estimated values of the useful power and the wind power density for the wind micro-turbine, operating at a wind speed of 4.0m/s, which represents approximately the average value of the wind speed (obtained with the scale factor of the Weibull function), are respectively 41 W and 0.226 W/m .